STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (STUDI KASUS USAHA PENGOLAHAN LELE UMKM SEDAP BAKAT, PEKANBARU) - Dyah Eka Kusumaningtyas; Suarman Suarman; RM Riadi RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study aims to analyze the development strategy of micro, small, medium enterprises Sedap Bakat. The subject of this study is Micro, Small, Medium Enterprises Sedap Bakat in Pekanbaru. The instruments of data collection were an open quetionnare and interviews. Data ware analyzed by using SWOT matrix. The result showed that the alternative strategies that can be applied by the company such as increasing the quality of products and services, expanding the market, rinning professional management system, increasing production capacity and increasing manpower by utilizing aid or loans to financial institutions, increasing promotion with social media, efficiency of production costs according to taste and needs of consumers, and open an outlet at public area. The result analysis shows that company has the strength that can be utilized in reaching the existing opportunity, with the main of strategies such as improve the quality of products and services, expanding the market.Keywords: Strategi of development, micro, small, medium enterprises